A Dyson-Schwinger study of the four-gluon vertex - Cyrol, Anton Konrad; Huber, Markus Q.; Smekal, Lorenz von (The European physical journal. C, Particles and fields, 2015)
We present a self-consistent calculation of the four-gluon vertex of Landau gauge Yang-Mills theory from a truncated Dyson-Schwinger equation. The equation contains the leading diagrams in the ultraviolet and is solved using as the only input results for lower Green functions from previous Dyson-Schwinger calculations that are in good agreement with lattice data. All quantities are therefore fixed and no higher Green functions enter within this truncation. Our self-consistent solution resolves the full momentum dependence of the vertex but is limited to the tree-level tensor structure at the moment. Calculations of selected dressing functions for other tensor structures from this solution are used to exemplify that they are suppressed compared to the tree-level structure except for possible logarithmic enhancements in the deep infrared. Our results furthermore allow one to extract a qualitative fit for the vertex and a running coupling.